Fabrication of poly-crystalline Si-based Mie resonators via amorphous Si on SiO2 dewetting. Issue 5 (14th January 2016) - Naffouti, Meher; David, Thomas; Benkouider, Abdelmalek; Favre, Luc; Ronda, Antoine; Berbezier, Isabelle; Bidault, Sebastien; Bonod, Nicolas; Abbarchi, Marco
Abstract : High-quality Si-based polycrystalline Mie resonators are fabricated on arbitrary silica substrates via solid-state dewetting. Abstract : We report the fabrication of Si-based dielectric Mie resonators via a low cost process based on solid-state dewetting of ultra-thin amorphous Si on SiO2 . We investigate the dewetting dynamics of a few nanometer sized layers annealed at high temperature to form submicrometric Si-particles. Morphological and structural characterization reveal the polycrystalline nature of the semiconductor matrix as well as rather irregular morphologies of the dewetted islands. Optical dark field imaging and spectroscopy measurements of the single islands reveal pronounced resonant scattering at visible frequencies. The linewidth of the low-order modes can be ∼20 nm in full width at half maximum, leading to a quality factor Q exceeding 25. These values reach the state-of-the-art ones obtained for monocrystalline Mie resonators. The simplicity of the dewetting process and its cost-effectiveness opens the route to exploiting it over large scales for applications in silicon-based photonics.